Intraplate crustal remelting as the genesis of Jurassic high-K granites in the coastal region of the Guangdong Province, SE China - Huang, Hui-Qing; Li, X.; Li, Zheng-Xiang; Li, W. (Pergamon-Elsevier Science Ltd, 2013)
The origin and tectonic significance of high-K granites (>3 wt% K2O at 70 wt% SiO2), calc-alkaline I-type granites in particular, remain controversial. This paper takes granitic plutons distributed in the coastal region of the Guangdong Province of southeastern China as examples to explore the genesis of such rocks. SIMS zircon U–Pb geochronological data show that the granites were emplaced at 166–159 Ma. These granites can be subdivided generally into two groups on the basis of integrated mineralogical, geochemical, whole-rock Sr–Nd isotopic and in situ zircon Hf–O isotopic studies. The group A granites (SiO2 = 64–72 wt%) are characterised by their common occurrence of amphibole (±titanite) and dominantly metaluminous feature (A/CNK = 0.85–1.03). They are high in K2O (3.5–7.0 wt%) and K2O/Na2O (>1), and have trace element concentrations (e.g., Nb, Y, Zr and Ga) similar to typical I-type granites in the Lachlan Fold Belt, southeastern Australia. Their whole-rock ISr (0.7057–0.7077) and εNd(t) (−6.46 to −3.13) are less evolved than many coeval granites in this region. As in situ zircon Hf–O isotopes show little evidence of magma mixing, these granites with low zircon δ18O (6.3−7.9‰) and high εHf(t) (−5.9 to −0.2) could have been generated from melting of oxidised high-K basaltic rocks.The group B granites, emplaced to the east of group A granites, are dominantly weakly peraluminous (A/CNK = 1.00–1.05). They have higher SiO2 (70–76 wt%), less common or absence of amphibole, higher zircon δ18O (6.6−9.0‰) and lower εHf(t) (−11.4 to −5.9) than the group A granites. Zircon Hf–O isotope data reveal that the group B granites contain higher percentage of supracrustal materials than those of the group A, but the variations of major and trace elements do not support an assimilation and fractional crystallization (AFC) model. Instead, the group B granites, with features transitional between typical I-type and S-type granites, were most likely formed in a region where there was physical juxtaposition between infracrustal metaluminous and supracrustal peraluminous source rocks. Thus, granites of both groups represent products of crustal reworking likely due to asthenosphere upwelling and/or underplating and intrusion of mafic magmas. The close association in time and space of these granites with OIB-like basaltic rocks and the secular compositional change of Jurassic basaltic rocks in the region suggest that these rocks probably formed in an intraplate extensional setting resulted from the delamination of a flat-subducted oceanic slab.